The Use of ICT by governments: a proposed research agenda based on the academic production an don national practice - Cortez da Cunha, Maria Alexandra Viegas; Miranda, Paulo Roberto de Mello (Organizações & Sociedade, 2013)
Government is a main player in society. The research in the use and social implicationsof Information and Communication Technologies - ICT have gotten space inacademy, as well as new methodological approaches in these studies. This essayis a proposal of agenda to the research in the use and social implications of ICTby governments in Brazil. It emerges from the reflections about national academicproduction and projects being implemented by governments in Brazil. It proposessome investigation areas - electronic governance, electronic public services, the useof ICT in public administration, both in public policies in "finalistic areas" and in publicmanagement policies, and yet its use to enhance democratic practices. Other projectsgot relevance in national scenery and became investigation fields - ICT governance in public sector, digital inclusion initiatives, digital cities projects, and the use of ICTto improve economic activities, both in the ICT industry itself (hardware, software,services, content), and in its use in traditional economic sectors, those which arenatural or planned vocation of a city, region state or nation. In order to implementthis agenda, methodological approaches are proposed, that support a comprehensiveanalysis and a critical perspective of both the scientific production, and the use of ICTby Brazilian governments and their implications to the society.